Violence prevention in schools: Resilience promotion in the framework of a European practice research project - Katharina Rauh; Klaus Fröhlich-Gildhoff (Escola Superior de Educação de Paula Frassinetti, 2014)
The following article presents the theoretical background, design and evaluation results of the international practice research project Strong implementing strategies of violence prevention in schools by means of resilience promotion. After presenting the results from the quantitative and qualitative results briefly, success factors for the implementation of a prevention strategy are highlighted